Case reportPatient with suspected hyperIgE syndrome – a case report - Rosińska, Anna; Czarnecka-Operacz, Magdalena; Silny, Wojciech (Advances in Dermatology and Allergology/Postępy Dermatologii i Alergologii, 2008)
The hyper-immunoglobulin E syndrome (HIES, Job’s syndrome) is a primary immunodeficiency disease. The clinical triad of symptoms such as elevated serum IgE-level (>2000 IU/ml), recurrent bacterial and viral infections and recurrent pneumonias are typical for this entity. Most cases of HIES are sporadic, but autosomal recessive (AR) and autosomal dominant (AD) inheritance have also been described. There have been more than 200 HIES patients documented in the literature. In most sporadic and AD cases the HIES clinical triad is part of a multisystem disorder including abnormalities in the soft tissue, skeletal and dental systems. Patients with AR HIES suffer more often from severe viral infections (molluscum contagiosum) and severe neurological complications. This paper presents the case of a 1-year-old girl, admitted to the Department of Dermatology due to erythrodermia in the course of atopic dermatitis with coexistent eczema herpeticum. The child has been erythrodermic for the last 5 years. There has been a positive family history of allergy. The child has often suffered from recurrent bacterial, viral and fungal infections as well as bronchial asthma. The total serum IgE concentration was 51 375 KU/l.